Jewish childhood in Kraków : a microhistory of the Holocaust - Sliwa, Joanna (Rutgers University Press, 2021)
"Jewish Childhood in Kraków is the first history to tell the wartime history of Kraków through the lens of Jewish children's experiences. Historian Joanna Sliwa examines what children under 14 years old experienced when the second World War broke out. How did they cope? What roles did they take on? In this story, children assume center stage as historical actors whose recollections and experiences deserve to be told, analyzed, and treated seriously. Sliwa scours archives on three continents to tell their story, gleaning evidence from the records of the German army, Polish neighbors, Jewish community and family, and the children themselves. It is through the children and their recollections that this book explores the events and processes that framed the Holocaust in German-occupied Poland in general, and in Kraków in particular. A microhistory of a place, a people, and daily life, this book plumbs the decisions and behaviors of ordinary people in extraordinary times. It illuminates the complex relations between Jews and non-Jews in response to the Holocaust in Kraków and in German-occupied Poland more broadly. And it offers a window onto human relations and ethnic tensions in times of rampant violence. Ultimately, Jewish Childhood in Kraków is an effort both to understand the past and to reflect on the position and responses of young people during humanitarian crises"